FORMATIVE ASSESSMENT IN THE MERDEKA CURRICULUM ISLAMIC RELIGIOUS EDUCATION LEARNING AT SDN BUMIAYU MAGELANG - Widya Wulandari; Maemonah Maemonah (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2023)
The Merdeka curriculum emphasizes the importance of integration with formative assessment, as a learning cycle. Formative assessment has the potential to support the teaching and learning process in the classroom so that the use of assessment for formative purposes is intended to integrate the learning process of students and improve learning outcomes. This study aims to determine the process and preparation of teachers in optimizing especially formative assessments in the Merdeka curriculum in PAI learning at SDN BumiAyu Magelang. This study uses a qualitative approach. The data collection technique, namely literature study, is adapted to the focus of research such as books, journals, the Merdeka curriculum assessment guide from the Ministry of Education and Culture. Collection of interview data for grade 4 PAI teachers who have implemented the Merdeka curriculum in the 2022/2023 odd semester at Bumiayu Magelang Elementary School. The results and discussion in optimizing the formative assessment of Islamic Religious Education subject teachers at SDN Bumiayu Magelang is that the feedback technique has been felt to be very good and has given good results. The teacher must also have many strategies in providing feedback, so that during the learning process students do not feel bored. This assessment is carried out to achieve the quality of student achievement produced, so the teacher must own and understand the scoring made by him.